Nurse's contributions in education and care management in conservative treatment in nephrology: integrative review - Lima, Rafael Abrantes de (2021)
Chronic Kidney Disease is a global public health problem, and its main factors are systemic arterial hypertension and secondly, diabetes mellitus associated or not with other factors such as alcoholism, smoking, and population aging. The aim of this study is to identify the scientific evidence on nurses' contributions to education and to managing the care of nephropathic clients undergoing conservative treatment. Methodology: this is an integrative review, whose method allows the analysis of multiple studies and, thus, the synthesis, which contributes to draw conclusions on a given theme. Results: the research was composed of nine articles, 2013 was the year that presented the highest number of publications including three articles, as for the country of origin, Brazil stands out with eight articles published and Revista RENE was the journal with the highest number of articles published. The fundamental role of nurses inserted in conservative treatment outpatient facilities stands out, which articulates with the other professional categories in search of better conditions and quality. It highlights a need to know the patient’s perspective in relation to chronic kidney disease, to better share the decisions to be made about treatment, support network and health professionals.